The Effect of Health Education on WUS Knowledge about Fluor Albus at the Patumbak Health Center in 2021 - Herlia Sumardha Nasution; Fithriani Fithriani; Dori Fahma Harahap (Institute of Computer Science (IOCS), 2021)
Many women of childbearing age (WUS) think that vaginal discharge is normal. One of the reasons for this assumption is the lack of knowledge of women of childbearing age (WUS) about the impact of vaginal discharge. This study aims to determine the effect of Health Education on WUS Knowledge about Fluor Albus at the Patumbak Health Center in 2021. This research is a quantitative research with Pre-Experimental Design with a one-group pretest-posttest design approach. This research has been carried out on July 11, 2021 to July 24, 2021. The population is 84 people. Sampling using purposive sampling with a sample of 50 people. The results showed that WUS Knowledge about Fluor Albus before being given Health Education at the Patumbak Health Center in 2021 was the majority poor, WUS Knowledge about Fluor Albus after being given Health Education at the Patumbak Health Center in 2021 was the majority good. Based on the results of the paired sample t-test, the p value = 0.001 <0.05. So it can be concluded that there is an influence of Health Education on WUS Knowledge about Fluor Albus at the Patumbak Health Center in 2021. Suggestions in this research Patumbak Health Center make a planned program in the provision of health education to increase knowledge and understanding of WUS, especially about vaginal discharge in the work area of ​​the Patumbak Health Center.